The Measurement of Journalistic Role Enactments: A Study of Organizational Constraints and Support in For-Profit and Nonprofit Journalism. (September 2016) - Carpenter, Serena; Boehmer, Jan; Fico, Frederick
Media scholars have primarily assessed journalistic role perceptions through the survey method. We propose conceptual and operational definitions for four role enactments observable through content analysis: dissemination, interpretative, adversarial, and mobilization. We also examined how journalistic role enactments in stories related to organization type (nonprofit and for-profit) and reporter workload. Results show that nonprofit journalists were more likely to include interpretation in stories, whereas for-profit journalists were more likely to enact the dissemination and mobilization roles. In addition, as reporter story number increases, it significantly predicted enacting the dissemination role, while suppressing the interpretative role, and especially the adversarial role enactment.